Lifetime occupational history and risk of endometriosis - Marino, Jennifer L.; Holt, Victoria L.; Chen, Cynthia; Davis, Scott (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVES ': 'Endometriosis is the presence of functioning endometrial glands and stroma outside the uterine cavity, most often in the pelvic peritoneal cavity. Women with endometriosis commonly have dysmenorrhea, dyspareunia, pain, menorrhagia, and/or metrorrhagia. Disease complications can include adhesions, chronic pain, and infertility. In this exploratory case-control study, we investigated the relationship between lifetime occupational history and surgically confirmed endometriosis in a population-based sample. ' ' METHODS ': 'We conducted interviews with participants, all reproductive-aged female members of a large health-maintenance organization who were first diagnosed with surgically confirmed endometriosis between April 1, 1996 and March 31, 2001. Interviews were also conducted with randomly selected controls, reproductive-aged female enrollees of the same organization from the same time period. Each reported job was coded using US Census Occupations and Industries codes, and classified into categories. We used unconditional logistic regression to compare having worked in a given job class with never having done so. ' ' RESULTS ': 'Our study found that an increased risk of endometriosis was associated with having worked as a flight attendant, service station attendant, or health worker, particularly as a nurse or health aide (flight attendant: odds ratio (OR) 9.80, 95% CI 1.08–89.02; service station attendant: OR 5.77, 95% CI 1.03–32.43; health worker: OR 1.49, 95% CI 1.03–2.15). Income and education did not make a difference in the OR estimates for the occupations examined. ' ' CONCLUSIONS ': 'This exploratory study suggested that there might be an associated risk of endometriosis for those women who have worked as a flight attendant, service station attendant, or health worker, particularly a nurse.
Keywords: case–control study; endometriosis; health; occupational exposure; occupational history; risk; woman